Role of glipizide therapy on oxidative stress parameters in the patient with Type-II diabetes mellitus - Malam, Prakash P.; Kantharia, Naresh D.; Zala, Ashishkumar C.; Amin, Anand J.; Deoghare, Shashank B.; Gajera, Chirag N. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Oxidative stress has an important role in the pathophysiology of diabetes mellitus (DM) Type-II. Oxidative stress has an important role in the progression of DM Type-II and its related complications such as retinopathy, neuropathy and many others. The present study was carried out to evaluate the effect of glipizide therapy on oxidative stress parameters in Type-II DM. Methods: Thirty newly diagnosed diabetes patients were given glipizide therapy on 1st day and continue for 3 months. 30 non-diabetic healthy volunteers served as a control. Plasma malondialdehyde (MDA), superoxide dismutase (SOD) and catalase levels were measured at the time of enrollment and at the end of 3 months of glipizide treatment. Result: Theresults are analyzed using paired t-test. Plasma MDA was significantly increased, whereas SOD and catalase were significantly reduced in newly diagnosed diabetic patients as compared to control. After 3 months of glipizide therapy, plasma MDA was significantly reduced, whereas SOD and catalase were significantly increased. Conclusion: Glipizide therapy significantly reduced oxidative free radicals and increased antioxidant mechanism, which reduced oxidative stress, progression DM-II and its related complication.